Adams, Eddie (London, 2011)
2011 "Adams, Eddie", 2011, HistoryTalk Eddie Adams started work in 1951 aged 15 as a sheet metal worker at Vulcan Sheet Metal Works in Latimer Road in west London. He notes the high concentration of small industrial factories. He moved to Heinz factory in Harlesden, Great Western Railway at Paddington and in a local bookshop but continued to change jobs during these years of stable employment. He also began to acquire electrical wiring skills. He became an electrician and began working all over London including the Ministry of Works and the Royal Chelsea Hospital in 1960. He worked at Fords in Dagenham, doing electrical contract work and, in 1974 took a 'career break' to bring up his daughter. He later worked at North Kensington Law Centre (the first in the UK).